ALICE detector status and upgrade plans - Oyama, Ken (HCP 2012 - Hadron Collider Physics Symposium 2012, 2013)
ALICE is a general-purpose detector dedicated to heavy-ion physics at the CERN LHC. It is designed to address the physics of strongly interacting matter and the quark-gluon plasma at extreme values of energy density and temperature in nucleus-nucleus collisions. An overview of ALICE experiment, its current status and performance, and the future upgrade plan will be discussed.